Negative electrode active material and rechargeable lithium battery including same
By using silicon nanoparticles and amorphous carbon coating with optimized characteristics in the negative electrode active substance of lithium batteries, the problem of insufficient energy density and cycle life of lithium batteries in the prior art is solved, and the effect of higher energy density and longer cycle life is achieved.
Patent Information
- Application Number
- CN202411140220.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-25
- Filing Date
- 2024-08-20
- Publication Date
- 2025-02-25
AI Technical Summary
It is difficult to develop rechargeable lithium batteries with high energy density and light weight, especially in the negative electrode active substances.
Negative electrode active substances including silicon nanoparticles and amorphous carbon coatings are used, which have specific spherical, pore structure and specific surface area characteristics, through which the electrode performance is optimized.
A higher energy density and longer cycle life are achieved, while reducing the expansion of the battery during charging and discharging, improving the overall battery performance.
Smart Images

Figure CN119517951A_ABST
Abstract
Description
Technical Field
[0001] Embodiments relate to a negative electrode active material and a rechargeable lithium battery including the negative electrode active material. Background Art
[0002] Recently, the rapid increase in electronic devices such as mobile phones, laptop computers, and electric vehicles using batteries has caused a surprising increase in demand for rechargeable batteries with relatively high capacity and light weight. There has been a need to develop batteries with high energy density, which in turn requires high-capacity negative electrode active materials. Attempts have been made to use Si negative electrode active materials as high-capacity negative electrode active materials. Summary of the invention
[0003] An embodiment relates to a negative electrode active material, the negative electrode active material comprising: silicon nanoparticles, including an amorphous carbon coating on surfaces of the silicon nanoparticles; and pores, wherein the negative electrode active material has a sphericity expressed by Equation 1 of about 0.9 to about 1.0, the pores include mesopores, and a ratio of a mesopore volume of the negative electrode active material to a total pore volume is about 30% or more and less than about 70%, and [Equation 1] Sphericity (S) = 4π × A / B 2 In Equation 1, A is the area of the negative electrode active material, and B is the perimeter of the shape of the negative electrode active material.
[0004] The mesopores may have a size of about 2 nm to about 50 nm.
[0005] The ratio of the mesopore volume of the negative electrode active material to the total pore volume may be about 30% to about 68%.
[0006] The negative electrode active material may have a span defined by Equation 2 of about 1.1 to about 1.6, and [Equation 2] Span = (D90-D10) / D50 In Equation 2, D10 refers to the diameter of the negative electrode active material particles whose cumulative volume is 10% by volume in the particle size distribution, D50 refers to the diameter of the negative electrode active material particles whose cumulative volume is 50% by volume in the particle size distribution, and D90 refers to the diameter of the negative electrode active material particles whose cumulative volume is 90% by volume in the particle size distribution.
[0007] The span of the negative electrode active material may be from about 1.1 to about 1.55.
[0008] The span of the negative electrode active material may be from about 1.1 to about 1.5.
[0009] The negative electrode active material may have a sphericity of about 0.92 to about 0.98.
[0010] The negative electrode active material may have a sphericity of about 0.92 to about 0.95.
[0011] The negative electrode active material may further include a polymer layer on the amorphous carbon coating.
[0012] The polymer layer may include polyvinyl alcohol and polyacrylic acid.
[0013] The polymer layer may include a copolymer of polyvinyl alcohol and polyacrylic acid.
[0014] The copolymer may include a cross-linked copolymer of polyvinyl alcohol and polyacrylic acid.
[0015] The negative electrode active material may have a 2 / g to about 2m 2 / g specific surface area (BET).
[0016] The negative electrode active material may have a 2 / g to about 2m 2 / g specific surface area (BET).
[0017] The negative electrode active material may have a 2 / g to about 1.5m 2 / g specific surface area (BET).
[0018] The total pore volume of the negative electrode active material can be about 0.001 cm 3 / g to about 0.05cm 3 / g.
[0019] The silicon nanoparticles may have a particle size of about 1 nm to about 1000 nm.
[0020] The amorphous carbon coating layer may have a thickness of about 1 nm to about 2 μm.
[0021] Embodiments may be implemented by providing a rechargeable lithium battery including: a negative electrode including the negative electrode active material; a positive electrode; and an electrolyte.
[0022] The negative electrode may include the negative electrode active material as a first negative electrode active material, and further include crystalline carbon as a second negative electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Features will become apparent to those skilled in the art by describing in detail exemplary embodiments with reference to the accompanying drawings, in which: Figure 1is an exploded perspective view of a rechargeable lithium battery according to an embodiment. DETAILED DESCRIPTION
[0024] Example embodiments will now be described more fully hereinafter with reference to the accompanying drawings; however, example embodiments may be implemented in different forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey exemplary implementations to those skilled in the art.
[0025] In the accompanying drawings, the sizes of layers and regions may be exaggerated for clarity of illustration. It will also be understood that when a layer or element is referred to as being "on" another layer or substrate, it can be directly on the other layer or substrate, or there may also be intervening layers. It will also be understood that when a layer is referred to as being "under" another layer, it can be directly "under" the other layer, and there may also be one or more intervening layers. In addition, it will be understood that when a layer is referred to as being "between" two layers, it can be the only layer between the two layers, or there may also be one or more intervening layers. The same reference numerals always represent the same elements. Unless the context clearly indicates otherwise, statements in the singular include statements in the plural.
[0026] The term "combination thereof" may include mixtures, laminates, composites, copolymers, alloys, blends, reactants of the components.
[0027] The terms "include", "comprising" or "having" are intended to specify the presence of a characteristic, quantity, step, component element or combination thereof performed, but it should be understood that the possibility of the presence or addition of one or more other characteristics, quantities, steps, component elements or combinations thereof is not precluded. When an element is referred to as being "directly on" another element, there are no intervening elements.
[0028] In some embodiments, herein, a "layer" includes a shape that is completely formed on the entire surface or a surface of a portion of the shape when viewed from a plan view.
[0029] As used herein, "or" should not be interpreted in an exclusive sense, for example, "A or B" may be interpreted to include A, B, A+B, etc.
[0030] In the present disclosure, when no definition is otherwise provided, the particle size or particle size may refer to the average particle size. The average particle size represents the average value of the diameter of the particles according to the cumulative volume in the particle size distribution of the particles included in the negative electrode active material. The average particle size (D50) can be measured by a suitable method, such as by a particle size analyzer, or by a transmission electron microscope image or a scanning electron microscope image. In some embodiments, a dynamic light scattering measurement device can be used for data analysis, and the number of particles can be counted for each particle size range, whereby the average particle size (D50) value can be easily obtained by calculation.
[0031] The negative electrode active material according to some embodiments may include pores and silicon nanoparticles having an amorphous carbon coating on surfaces of the silicon nanoparticles. The negative electrode active material may have a sphericity (S) represented by Equation 1 of about 0.9 to about 1.0.
[0032] [Equation 1] Sphericity (S) = 4π × A / B 2 Here, in Equation 1, A may be the area of the negative electrode active material, and B may be the perimeter of the shape of the negative electrode active material.
[0033] In an embodiment, the pores may include mesopores, and a ratio of the volume of the mesopores of the negative electrode active material relative to the total pore volume may be about 30% or more and less than about 70%.
[0034] In an embodiment, the ratio of the mesopore volume may be defined by (mesopore volume / total pore volume)×100%, and may be, for example, about 30% or more and less than about 70%, or may be about 30% to about 68%.
[0035] In an embodiment, the total pore volume and the mesopore volume can be quantitatively measured, for example, by a BJH (Barrett-Joyner-Halenda) analysis apparatus. For example, the pore volume value per pore width (e.g., diameter) can be plotted via BJH analysis, and the volume of the pore width (e.g., diameter) from about 2 nm to about 50 nm is added to obtain the volume of the mesopores.
[0036] In an embodiment, the total pore volume may represent, for example, the total volume of all pores of any size in the negative electrode active material (including mesopore volume). In an embodiment, the total pore volume may be, for example, about 0.001 cm 3 / g to about 0.05cm 3 / g, or about 0.005 cm 3 / g to about 0.05cm 3 / g, and may be a value measured by BJH.
[0037] Mesopores may refer to pores having a size of, for example, about 2 nm to about 50 nm. In an embodiment, the pores may include macropores having a size greater than about 50 nm. Pores having a size exceeding about 50 nm may be classified as macropores, so that it may not be necessary to limit the maximum value of the macropores, but it may be up to about 500 nm. It may be desirable that these macropores be included in an amount of about 1% by volume or less and at least 0% by volume based on the total pore volume, for example, macropores may be substantially excluded in the negative electrode active material.
[0038] The pores may also include micropores having a size, for example, greater than about 0 nm and less than about 2 nm. The volume of the micropores included in the negative electrode active material may correspond to the volume excluding the mesopore volume from the total pore volume, or if the pores include macropores, the volume excluding the mesopore volume and the macropore volume from the total pore volume. The pore size may represent the average diameter of the pores or the length of the longest axis of the pores.
[0039] In embodiments, mesopores, micropores, and macropores may be classified according to the size of the pores.
[0040] The negative electrode active material according to one or more embodiments may have a spherical shape, which may help it to be well distributed throughout the negative electrode, thereby helping to reduce expansion during charge and discharge. In an embodiment, the negative electrode active material may be used by mixing the negative electrode active material with crystalline carbon, whereby the spherical negative electrode active material may be better intercalated between the crystalline carbon, thereby being more evenly distributed throughout the negative electrode.
[0041] The negative electrode active material according to one or more embodiments may have a sphericity (S) representing a spherical shape expressed by Equation 1 of, for example, about 0.9 to 1.0.
[0042] [Equation 1] Sphericity (S) = 4π × A / B 2 In Equation 1, A may be, for example, the area of the negative electrode active material, and B may be, for example, the perimeter of the shape of the negative electrode active material. In an embodiment, B may be, for example, the perimeter of the actual shape of the negative electrode active material.
[0043] In an embodiment, the sphericity of the negative electrode active material may be a value obtained by projecting a three-dimensional particle onto a two-dimensional plane. In an embodiment, the sphericity may be a ratio of the boundary of the actual particle shape to the boundary of a circle having the same area as the actual particle shape.
[0044] Area A may refer to the area of a circle having the same circumference as B, which may be determined after obtaining a SEM image of the electrode cross section using, for example, CP-SEM (controlled pressure scanning electron microscope) and obtaining the actual circumference (B) of the particle, for example, via the Image J program. In an embodiment, if the particle shape is a perfect sphere, the actual circumference may be the circumference, and if the particle shape is not a perfect sphere and has a convex area, the actual circumference may also be the length obtained along the circumference.
[0045] The sphericity of the negative electrode active material according to one or more embodiments may be, for example, about 0.92 to about 0.98, or about 0.92 to about 0.95. Maintaining the sphericity of the negative electrode active material within the above range may help ensure that expansion can be further effectively suppressed during charge and discharge.
[0046] The negative electrode active material according to one or more embodiments may have a span defined by Equation 2 of about 1.1 to about 1.6.
[0047] [Equation 2] Span = (D90-D10) / D50 In Equation 2, D10 may refer to, for example, the diameter of negative electrode active material particles having a cumulative volume of 10% by volume in the particle size distribution, D50 may refer to, for example, the diameter of negative electrode active material particles having a cumulative volume of 50% by volume in the particle size distribution, and D90 may refer to, for example, the diameter of negative electrode active material particles having a cumulative volume of 90% by volume in the particle size distribution.
[0048] In one or more embodiments, the span can be, for example, about 1.1 to about 1.55, or about 1.1 to about 1.5.
[0049] Maintaining the span of the negative electrode active material within the above range can help ensure that the negative electrode active material does not substantially include any fine powder. In an embodiment, fine powders having a size of, for example, about 1 μm or less and irregular shapes may be rarely included so that a low specific surface area can be exhibited, thereby reducing side reactions with the electrolyte and improving cycle life.
[0050] The negative electrode active material according to one or more embodiments may have a low specific surface area, for example, a low BET specific surface area, and its specific surface area may be, for example, about 0.5 m 2 / g to about 2m 2 / g, about 0.8m 2 / g to about 2m 2 / g or about 0.8m 2 / g to about 1.5m 2 / g. This specific surface area may be lower than, for example, about 3 m 2In one or more embodiments, ASAP2020 can be used to measure the BET specific surface area.
[0051] In one or more embodiments, the particle size of the silicon nanoparticles may be, for example, about 10 nm to about 1000 nm, and according to another embodiment, may be, for example, about 10 nm to about 200 nm, or about 20 nm to 150 nm. Maintaining the average particle size of the silicon nanoparticles within this range may help ensure that the extreme volume expansion caused during charging and discharging may be suppressed, and the breakage of the conductive path due to the fragmentation of the particles may be prevented.
[0052] In an embodiment, in the amorphous carbon coating, the amorphous carbon may be, for example, soft carbon, hard carbon, mesophase pitch carbide, sintered coke, or a combination thereof. The thickness of the amorphous carbon coating may be, for example, about 1 nm to about 2 μm, about 1 nm to about 500 nm, about 10 nm to about 300 nm, or about 20 nm to about 200 nm. Keeping the thickness of the amorphous carbon coating within the above range may help ensure that the silicon volume expansion may be effectively suppressed during charging and discharging. In one or more embodiments, the thickness of the amorphous carbon coating may be measured by an SEM image or a TEM image of a cross section of the silicon-carbon composite, but it may not be limited and may be measured by any technique as long as the thickness of the amorphous carbon coating is measured.
[0053] In the negative electrode active material, the amount of the silicon nanoparticles may be, for example, about 55 wt % to about 64 wt %, or about 58 wt % to about 62 wt %, based on the total weight of the negative electrode active material. The amount of the amorphous carbon coating may be, for example, about 36 wt % to about 45 wt %, or about 38 wt % to about 42 wt %, based on the total weight of the negative electrode active material.
[0054] In an embodiment, the negative electrode active material according to one or more embodiments may further include a polymer layer on the amorphous carbon coating. The polymer layer may include, for example, a copolymer of polyvinyl alcohol and polyacrylic acid, and the copolymer may be a cross-linked copolymer in which the polyvinyl alcohol and the polyacrylic acid are cross-linked. Including a polymer layer in the negative electrode active material layer may help ensure that the volume expansion of the negative electrode active material can be effectively suppressed during charging and discharging.
[0055] The polymer layer may include, for example, polyvinyl alcohol and polyacrylic acid, which may help ensure that the electrolyte may be prevented from being impregnated into the interior of the negative electrode active material (e.g., into the empty space or pores of the negative electrode active material) during charge and discharge, thereby further effectively inhibiting the side reaction of the negative electrode active material with the electrolyte. Polyvinyl alcohol and polyacrylic acid may each be a water-based polymer and an environmentally friendly polymer.
[0056] In an embodiment, the polymer layer may include a copolymer of polyvinyl alcohol and polyacrylic acid, for example, may be a cross-linked polymer, for example, a cross-linked copolymer in which polyvinyl alcohol and polyacrylic acid are cross-linked. In an embodiment, the polymer of the polymer layer may be a cross-linked polymer of polyvinyl alcohol and polyacrylic acid. Including a cross-linked polymer of polyvinyl alcohol and polyacrylic acid as a cross-linked polymer in the polymer layer can ensure that the polymer layer can not be dissolved in a solvent (e.g., water) used to prepare the negative electrode active material layer, and thus the polymer layer can be maintained.
[0057] In the negative electrode active material according to some embodiments, if the silicon nanoparticles and the amorphous carbon coating are referred to as a silicon-carbon composite, the amount of the polymer layer may be from about 0.01 parts by weight to about 3 parts by weight, or from about 1.2 parts by weight to about 2.1 parts by weight based on 100 parts by weight of the silicon-carbon composite. Maintaining the amount of the included polymer layer within the above range may help ensure that the effect from the polymer layer may be obtained to a greater extent.
[0058] In the polymer layer, the weight ratio of polyvinyl alcohol to polyacrylic acid may be, for example, about 3:97 to about 40:60, about 6:94 to about 40:60, or about 6:94 to about 20:80. Maintaining the mixing ratio of polyvinyl alcohol to polyacrylic acid within the above range (e.g., maintaining the amount of polyacrylic acid higher than the amount of polyvinyl alcohol) may help ensure that cycle life characteristics may be further enhanced.
[0059] In an embodiment, the ratio of the functional groups included in the polyvinyl alcohol and the polyacrylic acid included in the polymer layer can be appropriately adjusted. In an embodiment, the molar ratio of the OH group included in the polyvinyl alcohol to the COOH group included in the polyacrylic acid can be, for example, about 5:95 to about 50:50, or about 10:90 to about 30:70. Maintaining the molar ratio of the functional groups within the above range can help ensure that the effect of preparing the polymer layer can be further enhanced, and the cycle life characteristics can be further improved.
[0060] The negative electrode active material according to some embodiments may be prepared by the following steps.
[0061] Micron-sized silicon particles can be crushed to prepare nano-sized silicon primary particles. Crushing can be performed by suitable techniques such as ball milling. Crushing can be performed, for example, by using a dispersant. The dispersant can include, for example, stearic acid, boron nitride (BN), MgS, polyvinyl pyrrolidone (PVP) or a combination thereof. The amount of dispersant used can be an amount appropriate for the grinding of the silicon particles.
[0062] The particle diameter of the silicon primary particles may be, for example, about 1 nm to about 1000 nm, about 10 nm to about 1000 nm, about 10 nm to about 200 nm, or about 20 nm to about 150 nm.
[0063] The resulting mixture may be dried. The drying process may be performed, for example, by spray drying. The drying process performed by spray drying may produce a dried product having a more uniform particle size and a spherical shape, from which secondary particles in which primary particles are aggregated may be prepared. Maintaining a uniform particle size and a spherical shape of the dried product may help ensure that the amorphous carbon coating may be formed more uniformly over the entire surface.
[0064] The dried product may be mixed with an amorphous carbon precursor. The amorphous carbon precursor may be petroleum coke, coal coke, petroleum pitch, coal pitch, green coke, or a combination thereof.
[0065] The obtained product may be further subjected to compression molding, which can reduce the pores inside the negative electrode active material, thereby effectively suppressing side reactions.
[0066] The compression molding may be performed at a pressure sufficient to maintain the spherical shape of the final product (negative electrode active material) (eg, greater than about 0 MPa and about 30 MPa or less, greater than about 0 MPa and about 20 MPa or less, or about 5 MPa to about 20 MPa).
[0067] Compression molding can be performed by, for example, cold isostatic pressing (CIP). Performing compression molding within the above pressure range can help ensure that the pores can be appropriately reduced without generating fine powder while maintaining a spherical shape.
[0068] Then, the compression molded product can be carbonized. Carbonization can be performed, for example, at about 600° C. to about 1000° C. During carbonization, the dispersant can be removed. Carbonization can be performed, for example, under an N2 atmosphere, a helium atmosphere, or a combination thereof. As a result of carbonization, the amorphous carbon precursor can be converted into amorphous carbon, and the amorphous carbon can surround the surface of the compression molded product, thereby preparing an amorphous carbon coating.
[0069] Carrying out carbonization at the above temperature range can help ensure that excessive growth of Si particles can be suppressed, the formation of SiC can be suppressed, and the conductivity of amorphous carbon can be enhanced at the same time. In an embodiment, amorphous carbon can be inserted into the holes formed between the primary particles to be positioned on the surface of the primary particles, thereby surrounding the surface of the primary particles. Carrying out carbonization under the above atmosphere can help ensure that amorphous carbon can be effectively prepared while effectively suppressing oxidation of silicon and the formation of SiC, thereby reducing the resistance of the active material.
[0070] In an embodiment, instead of mixing the dried product with an amorphous carbon precursor, an amorphous carbon precursor gas may be used to vapor coat the dried product. This may allow an amorphous carbon coating to be formed on the surface of the product without an additional carbonization process. Therefore, after vapor coating is performed, compression may be performed. The compression conditions may be as described above.
[0071] If the negative electrode active material layer further includes a polymer layer, the prepared negative electrode active material (which may hereinafter be referred to as a silicon-carbon composite) may be further mixed with a polymer solution and dried, and then heat-treated.
[0072] The polymer solution may be prepared by mixing polyvinyl alcohol and polyacrylic acid in a solvent, and the solvent may be, for example, water, ethanol, or a combination thereof.
[0073] The mixing ratio of the silicon-carbon composite and the polymer solution may be appropriately adjusted to have the amount of the polymer in the prepared negative electrode active material and the mixing ratio of the polyvinyl alcohol and the polyacrylic acid.
[0074] The heat treatment may cause a condensation reaction of the OH group of the polyvinyl alcohol and the COOH group of the polyacrylic acid to crosslink the polyvinyl alcohol and the polyacrylic acid, thereby preparing a crosslinked polymer.
[0075] The heat treatment may be performed, for example, at about 150° C. to about 200° C. Performing the heat treatment within the above temperature range may help ensure that the condensation reaction (eg, cross-linking reaction) may occur well, thereby effectively preparing the cross-linked polymer.
[0076] Then, the heat-treated product may be pulverized. The pulverization may be performed, for example, using a sieve, so that the span (defined by equation 2) of the negative electrode active material is, for example, about 1.1 to about 1.6. In an embodiment, the pulverization may be performed to obtain an active material having a particle size such that the span obtained by D10, D50, and D90 of the active material is, for example, about 1.1 to about 1.6.
[0077] Another embodiment provides a rechargeable lithium battery including a negative electrode, a positive electrode, and an electrolyte.
[0078] The negative electrode may include a current collector and a negative electrode active material layer on the current collector, the negative electrode active material layer including the negative electrode active material according to one or more embodiments.
[0079] The negative electrode active material according to some embodiments may be included as a first negative electrode active material, and crystalline carbon may be included as a second negative electrode active material, for example. The mixing ratio of the first negative electrode active material and the second negative electrode active material may be about 80:20 to about 90:10 by weight. In an embodiment, the negative electrode active material may include a first negative electrode active material and a second negative electrode active material in a weight ratio of about 85:15 to about 90:10.
[0080] In the negative electrode active material layer, an amount of the negative electrode active material may be about 95 wt % to about 98 wt % based on the total 100 wt % of the negative electrode active material layer.
[0081] In an embodiment, the negative electrode active material layer may include a binder and may further include a conductive material. Based on the total weight of the negative electrode active material layer, the amount of the binder may be, for example, about 1 wt % to about 5 wt %. Based on the total weight of the negative electrode active material layer, the amount of the conductive material may be, for example, about 1 wt % to about 5 wt %.
[0082] The binder can help improve the binding properties between the negative electrode active material particles and between the negative electrode active material particles and the current collector. The binder can be a non-aqueous binder, an aqueous binder, or a combination thereof.
[0083] The non-aqueous binder may include, for example, ethylene propylene copolymer, polyacrylonitrile, polystyrene, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0084] The aqueous binder may include, for example, styrene-butadiene rubber (SBR), acrylated styrene-butadiene rubber (ABR), acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polypropylene, polyepichlorohydrin, polyphosphazene, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or a combination thereof.
[0085] In an embodiment, an aqueous binder may be used as a negative electrode binder, and a cellulose compound may be further included to help provide viscosity as a thickener. The cellulose compound may include, for example, carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or an alkali metal salt thereof. The alkali metal may be, for example, Na, K, or Li. The thickener may be included in an amount of about 0.1 to about 3 parts by weight based on 100 parts by weight of the negative electrode active material.
[0086] The conductive material can provide electrode conductivity, and a suitable conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material may be a carbon material, for example, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.; a metal material including a metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; a conductive polymer, such as a polyphenylene derivative; or a mixture thereof.
[0087] The current collector may include, for example, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0088] The positive electrode may include a current collector and a positive electrode active material layer formed on the current collector.
[0089] The positive electrode active material may include a lithiated intercalation compound that reversibly intercalates and deintercalates lithium ions. In an embodiment, one or more composite oxides of a metal (e.g., cobalt, manganese, nickel, or a combination thereof) and lithium may be used. In an embodiment, a compound represented by one of the following chemical formulas may be used. Li a A 1-b X b D 1 2 (0.90≤a≤1.8, 0≤b≤0.5); Li a A 1-b X b O 2-c1 D 1 c1 (0.90≤a≤1.8, 0≤b≤0.5, 0≤c1≤0.05); Li a E 1-b X b O 2-c1 D 1 c1 (0.90≤a≤1.8, 0≤b≤0.5, 0≤c1≤0.05); Li a E 2-b X b O 4-c1 D 1 c1 (0.90≤a≤1.8, 0≤b≤0.5, 0≤c1≤0.05); Li a Ni 1-b-c Co b X c D 1 α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α≤2); Li a Ni 1-b- c Co b Xc O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Co b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Mr b X c D 1 α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α≤2);Li a Ni 1-b-c Mr b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Mr b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni b HAVE BEEN c G d O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0.001≤d≤0.1);Li a Ni b Co c L 1 d G e O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0≤d≤0.5,0≤e≤0.1);Li a NiG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a CoG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mr 1-b G b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn2G bO4 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4 (0.90≤a≤1.8, 0≤g≤0.5); QO2; QS2; LiQS2; V2O5; LiV2O5; LiZO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2);Li a FePO4 (0.90≤a≤1.8).
[0090] In the above chemical formula, A can be Ni, Co, Mn or a combination thereof; X can be Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements or a combination thereof; D 1 can be O, F, S, P or a combination thereof; E can be Co, Mn or a combination thereof; T can be F, S, P or a combination thereof; G can be Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q can be Ti, Mo, Mn or a combination thereof; Z can be Cr, V, Fe, Sc, Y or a combination thereof; J can be V, Cr, Mn, Co, Ni, Cu or a combination thereof; L 1 It may be Mn, Al or a combination thereof.
[0091] The compound may have a coating on the surface, or may be mixed with another compound having a coating. The coating may include a coating element compound, such as an oxide of the coating element, a hydroxide of the coating element, an oxyhydroxide of the coating element, an oxygen-containing carbonate of the coating element, or a hydroxycarbonate of the coating element. The compound for the coating may be amorphous or crystalline. The coating element included in the coating may include, for example, Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating may be provided by a method that uses these elements in the compound without adversely affecting the properties of the positive electrode active material, and for example, the method may include any coating method such as spraying, dipping, etc.
[0092] In the positive electrode, the content of the positive electrode active material may be, for example, about 90 wt % to about 98 wt % based on the total weight of the positive electrode active material layer.
[0093] In an embodiment, the positive electrode active material layer may further include a binder and a conductive material.
[0094] The binder can help improve the bonding properties between the positive electrode active material particles and the bonding properties between the positive electrode active material particles and the current collector. Examples of the binder can include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.
[0095] The conductive material can provide electrode conductivity, and a suitable conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material may include carbon materials, for example, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.; metal materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof. The current collector may include, for example, Al.
[0096] The electrolyte may include a non-aqueous organic solvent and a lithium salt. The non-aqueous organic solvent may be used as a medium for transporting ions involved in the electrochemical reaction of the battery. The non-aqueous organic solvent may include, for example, carbonates, esters, ethers, ketones, alcohols or aprotic solvents.
[0097] The carbonate solvent may include, for example, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc., and the ester solvent may include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, etc. The ether solvent may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc., and the ketone solvent may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, and the like, and examples of aprotic solvents may include nitriles (such as R-CN (wherein R may be a C2 to C20 linear, branched, or cyclic hydrocarbon group, and may include a double bond, an aromatic ring, or an ether bond)), amides (such as dimethylformamide), dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane), sulfolane, and the like.
[0098] The organic solvent may be used alone or in a mixture. In an embodiment, the organic solvent may be used in a mixture, and the mixing ratio may be controlled according to desired battery performance.
[0099] In an embodiment, a non-aqueous organic solvent can be mixed and used, and a mixed solvent of a cyclic carbonate and a chain carbonate, a mixed solvent of a cyclic carbonate and a propionate solvent, or a mixed solvent of a cyclic carbonate, a chain carbonate and a propionate solvent can be used. The propionate solvent can be, for example, methyl propionate, ethyl propionate, propyl propionate or a combination thereof.
[0100] In an embodiment, a cyclic carbonate and a linear carbonate or a cyclic carbonate and a propionate solvent may be mixed, for example, in a volume ratio of about 1:1 to about 1:9, thereby improving the performance of the electrolyte solution. In an embodiment, a cyclic carbonate, a linear carbonate and a propionate solvent may be mixed, for example, in a volume ratio of about 1:1:1 to about 3:3:4. The mixing ratio of the solvent may be appropriately adjusted according to the desired properties.
[0101] In an embodiment, the organic solvent may further include an aromatic hydrocarbon solvent and a carbonate solvent. The carbonate solvent and the aromatic hydrocarbon solvent may be mixed together in a volume ratio of, for example, about 1:1 to about 30:1.
[0102] The aromatic hydrocarbon organic solvent may be an aromatic hydrocarbon compound represented by Chemical Formula 1.
[0103] [Chemical formula 1] In Chemical Formula 1, R1 to R6 may each independently be or include, for example, hydrogen, halogen, a C1 to C10 alkyl group, a halogenated alkyl group, or a combination thereof.
[0104] In an embodiment, the aromatic hydrocarbon organic solvent may include, for example, benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, Fluorotoluene, 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene or a combination thereof.
[0105] In an embodiment, the electrolyte may further include ethyl vinyl carbonate, vinylene carbonate, or an ethylene carbonate compound represented by Chemical Formula 2 as an additive for improving cycle life.
[0106] [Chemical formula 2] In Chemical Formula 2, R7 and R8 may each independently be or include, for example, hydrogen, halogen, cyano (CN), nitro (NO2) or C1 to C5 fluoroalkyl, provided that at least one of R7 and R8 is halogen, cyano (CN), nitro (NO2) or C1 to C5 fluoroalkyl, and R7 and R8 are not hydrogen at the same time.
[0107] In an embodiment, the ethylene carbonate compound may be or include, for example, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, fluoroethylene carbonate, etc. The amount of the additive for improving the cycle life characteristics may be used within an appropriate range.
[0108] Lithium salts dissolved in organic solvents can provide lithium ions to the battery, can substantially operate a rechargeable lithium battery, and can help improve the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include, for example, LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide (LiFSI)), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiN(C x F 2x+1 SO2)(C y F 2y+ 1SO2) (wherein, x and y are natural numbers, for example, integers from about 1 to about 20), lithium difluoro(bis(oxalato)phosphate, LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalato)borate: LiBOB) and lithium difluoro(oxalato)borate (LiDFOB). The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. Maintaining the concentration of the lithium salt within the above range may help ensure that the electrolyte may have excellent performance and lithium ion mobility due to optimal electrolyte conductivity and viscosity.
[0109] Depending on the type of rechargeable lithium battery, the separator may be located between the positive electrode and the negative electrode. The separator may include polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer having two or more layers thereof, and may be a mixed multilayer such as a polyethylene / polypropylene double-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.
[0110] Figure 1is an exploded perspective view of a rechargeable lithium battery according to an embodiment. In an embodiment, as shown in the drawings, the rechargeable lithium battery may be a prismatic battery, or may include batteries of various shapes such as a cylindrical battery, a pouch-type battery, and the like.
[0111] like Figure 1 As shown in FIG. 1 , a rechargeable lithium battery 100 according to an embodiment may include an electrode assembly 40 manufactured by winding a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 accommodating the electrode assembly 40. An electrolyte (not shown) may be impregnated with the positive electrode 10, the negative electrode 20, and the separator 30.
[0112] The following examples and comparative examples are provided to highlight the characteristics of one or more embodiments, but it will be understood that the examples and comparative examples will not be interpreted as limiting the scope of the embodiments, and the comparative examples will not be interpreted as being outside the scope of the embodiments. In addition, it will be understood that the embodiments are not limited to the specific details described in the examples and comparative examples.
[0113] (Example 1) Silicon particles having an average particle size of 8 μm were ball-milled to prepare primary particles having an average particle size D50 of 100 nm. The primary particles and stearic acid were mixed at a weight ratio of 20:80, and the mixture was spray-dried to prepare secondary particles having an average particle size D50 of 7 μm and pores.
[0114] The prepared secondary particles and petroleum asphalt were mixed in a weight ratio of 60:40, and the mixture was subjected to compression molding by cold isostatic pressing at a pressure of 10 MPa. Then, the obtained compression molded product was carbonized at 1000°C under N2 atmosphere.
[0115] The carbonized product was crushed using a filter so that the span defined by equation 2 was 1.1, thereby preparing a negative electrode active material as a silicon-carbon composite, the silicon-carbon composite including secondary particles having an average particle size D50 of 7 μm and a soft carbon coating coated on the secondary particles, in which silicon primary particles coated with soft carbon having a thickness of 30 nm and having an average particle size (D50) of 100 nm were aggregated. Based on the total weight of the negative electrode active material, the amount of silicon nanoparticles was 60 wt%, and the amount of soft carbon was 40 wt%. The D10, D50 and D90 of the negative electrode active materials of Examples 1 to 4 and Comparative Examples 1 to 4 were measured using a particle size analyzer (product name: LS 13320, manufacturer: Beckman Coulter). The results are shown in Table 1. Based on these values, the span defined by equation 2 was obtained, and it was found that the span was 1.1.
[0116] [Equation 2] Span = (D90-D10) / D50 From the cross-sectional image obtained from CP-SEM, the sphericity was measured via the Image J program and found to be 0.98. The total pore volume and mesopore volume of the prepared negative electrode active material were measured using a BJH (Barrett-Joyner-Halenda) analysis device.
[0117] BJH measurement was performed using a BJH (model: ASAP 2020, manufacturer: Micromeritics) analysis device to measure the amount of adsorption / desorption according to pressure change with respect to the sample while changing the pressure from 0 mmHg to 950 mmHg using nitrogen gas at liquid nitrogen temperature (-198°C).
[0118] The total pore volume results are shown in Table 1 as BJH, and the ratio of the mesopore volume to the total pore volume ((mesopore volume / total pore volume)×100%) was calculated. The results are shown in Table 1.
[0119] The prepared negative electrode active material is used as a first negative electrode active material, and a mixed negative electrode active material of 97.5 wt % of the first negative electrode active material and a natural graphite second negative electrode active material (the mixing ratio of the first negative electrode active material and the second negative electrode active material is 90:10 by weight), 1.5 wt % of carboxymethyl cellulose and 1 wt % of styrene-butadiene rubber are mixed in an aqueous solvent to produce a negative electrode active material layer slurry.
[0120] The negative electrode active material layer slurry was coated on a Cu foil current collector, dried, and pressed to prepare a negative electrode active material layer, thereby preparing a negative electrode.
[0121] A negative electrode, a lithium metal counter electrode and an electrolyte were used to fabricate a half-cell by general steps. The electrolyte was a 1M LiPF6 solution in a mixed solvent of ethylene carbonate and dimethyl carbonate (3:7 volume ratio).
[0122] The LiNi 0.88 Co0. 11 Al 0.01 A positive electrode active material layer slurry prepared by O2 positive electrode active material, 2 wt % of polyvinylidene fluoride binder and 2 wt % of Ketjen black conductive material was coated on an Al foil current collector, dried, and then pressed to prepare a positive electrode.
[0123] The negative electrode, positive electrode and electrolyte were used to manufacture coin-type full cells and pouch-type full cells by general steps. The electrolyte was a 1M LiPF6 solution in a mixed solvent of ethylene carbonate and dimethyl carbonate (3:7 volume ratio).
[0124] (Example 2) Negative electrodes, half cells, coin-type full cells and pouch-type full cells were manufactured by the same steps as in Example 1, except that the mixture of the prepared secondary particles and petroleum asphalt was compression molded by cold isostatic pressing at a pressure of 30 MPa and crushed to make the span 1.5 to prepare a negative electrode active material having a span of 1.5 and a sphericity of 0.95.
[0125] (Example 3) Negative electrodes, half cells, coin-type full cells and pouch-type full cells were manufactured by the same steps as in Example 1, except that the mixture of the prepared secondary particles and petroleum asphalt was compression molded by cold isostatic pressing at a pressure of 20 MPa and crushed to make the span 1.3 to prepare a negative electrode active material having a span of 1.3 and a sphericity of 0.96.
[0126] (Example 4) 6 wt % of polyvinyl alcohol and 94 wt % of polyacrylic acid were mixed in distilled water to prepare a polymer solution. The molar ratio of the OH group included in the polyvinyl alcohol to the COOH group included in the polyacrylic acid was 10:90.
[0127] The silicon-carbon composite prepared in Example 1 is mixed with a polymer solution, shaken, and then dried. The mixing ratio of the silicon-carbon composite and the polymer solution is adjusted so that the silicon-carbon composite is 97.1wt% and the polymer is 2.9wt%. The dried mixture is heat-treated at 150°C to prepare a negative electrode active material. In the prepared negative electrode active material, based on 100 parts by weight of the silicon-carbon composite, the amount of the polymer is approximately 3 parts by weight, the mixing ratio of polyvinyl alcohol and polyacrylic acid is a weight ratio of 6:94, and the molar ratio of the OH group included in the polyvinyl alcohol to the COOH group included in the polyacrylic acid is 10:90. The prepared negative electrode active material has a span of 1.1 and a sphericity of 0.97.
[0128] The prepared negative electrode active material is used as the first negative electrode active material, and a mixed negative electrode active material of 97.5 wt % of the first negative electrode active material and a natural graphite second negative electrode active material (the mixing ratio of the first negative electrode active material and the second negative electrode active material is 90:10 by weight) is used to manufacture a negative electrode, a half-cell, a coin-type full cell and a pouch-type full cell through the same steps as Example 1.
[0129] (Example 5) 6 wt % of polyvinyl alcohol and 94 wt % of polyacrylic acid were mixed in distilled water to prepare a polymer solution. The molar ratio of the OH group included in the polyvinyl alcohol to the COOH group included in the polyacrylic acid was 10:90.
[0130] The silicon-carbon composite prepared in Example 2 was mixed with a polymer solution, shaken, and then dried. The mixing ratio of the silicon-carbon composite and the polymer solution was adjusted so that the silicon-carbon composite was 97.1wt% and the polymer was 2.9wt%. The dried mixture was heat-treated at 150°C to prepare a negative electrode active material. In the prepared negative electrode active material, based on 100 parts by weight of the silicon-carbon composite, the amount of the polymer was approximately 3 parts by weight, the mixing ratio of polyvinyl alcohol and polyacrylic acid was a weight ratio of 6:94, and the molar ratio of the OH group included in the polyvinyl alcohol to the COOH group included in the polyacrylic acid was 10:90. The prepared negative electrode active material has a span of 1.5 and a sphericity of 0.95.
[0131] The prepared negative electrode active material is used as the first negative electrode active material, and a mixed negative electrode active material of 97.5 wt % of the first negative electrode active material and a natural graphite second negative electrode active material (the mixing ratio of the first negative electrode active material and the second negative electrode active material is 90:10 by weight) is used to manufacture a negative electrode, a half-cell, a coin-type full cell and a pouch-type full cell through the same steps as Example 1.
[0132] (Comparative Example 1) Negative electrodes, half cells, coin-type full cells and pouch-type full cells were manufactured by the same steps as in Example 1, except that compression molding was not performed on the prepared mixture of secondary particles and petroleum asphalt and crushing was performed to make the span 1.0 to prepare a negative electrode active material having a span of 1.0 and a sphericity of 0.97.
[0133] (Comparative Example 2) Negative electrodes, half cells, coin-type full cells and pouch-type full cells were manufactured by the same steps as in Example 1, except that the mixture of the prepared secondary particles and petroleum asphalt was compression molded by cold isostatic pressing at a pressure of 35 MPa and crushed to make the span 1.7 to prepare a negative electrode active material having a span of 1.7 and a sphericity of 0.96.
[0134] (Comparative Example 3) Negative electrodes, half cells, coin-type full cells and pouch-type full cells were manufactured by the same steps as in Example 1, except that the mixture of the prepared secondary particles and petroleum asphalt was compression molded by cold isostatic pressing at a pressure of 150 MPa to prepare a negative electrode active material having a span of 1.1 and a sphericity of 0.85 indicating non-sphericity.
[0135] (Comparative Example 4) Negative electrodes, half cells, coin-type full cells and pouch-type full cells were manufactured by the same steps as in Example 2, except that the mixture of the prepared secondary particles and petroleum asphalt was compression molded by cold isostatic pressing at a pressure of 150 MPa to prepare a negative electrode active material having a span of 1.5 and a sphericity of 0.85 indicating non-sphericity.
[0136] Experimental Example 1) Evaluation of charge and discharge efficiency The half cells according to Examples 1 to 5 and Comparative Examples 1 to 4 were charged and discharged once at 0.1 C in the range of 0.01 V to 1.5 V, and the ratio of the measured discharge capacity to the measured charge capacity was calculated. The results are shown in Table 2 as efficiency.
[0137] Experimental Example 2) Evaluation of cycle life characteristics The coin-type full cells according to Examples 1 to 5 and Comparative Examples 1 to 4 were charged and discharged once at 0.1C, once at 0.2C, and charged and discharged for 500 cycles at 1C in the range of 2.5 V to 4.2 V. The charge and discharge procedures and cutoff conditions were as follows.
[0138] Charging: Constant current-constant voltage, 4.2V / 0.01C cut-off Discharge: Constant voltage, 2.5V cut-off The ratio of the discharge capacity at the 500th cycle to the discharge capacity at the 1st cycle was calculated.
[0139] Experimental Example 3) Evaluation of expansion characteristics The pouch-type full batteries according to Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to one formation charge and discharge at 0.1C, and 25 cycles of charge and discharge at 1C. The ratio of the battery thickness after 25 cycles of charge and discharge relative to the battery thickness after formation charge and discharge was calculated. The results are shown in Table 2 as expansion (%).
[0140] Charging: Constant current-constant voltage, 4.2V / 0.01C cut-off Discharge: Constant voltage, 2.5V cut-off Table 1 Table 2 As shown in Tables 1 and 2, Examples 1 to 5 include negative electrode active materials in which the ratio of the mesopore volume to the total pore volume is 30% or more and less than 70%, have a spherical shape, and exhibit excellent efficiency, high cycle life, and low expansion characteristics.
[0141] However, Comparative Examples 1 and 2 included negative electrode active materials having a mesopore volume of 70% or 25% and exhibited deteriorated cycle life and high expansion characteristics.
[0142] Comparative Examples 3 and 4 include negative electrode active materials having a non-spherical shape and exhibiting degraded efficiency, extremely low cycle-life characteristics, and surprisingly high expansion characteristics.
[0143] By way of summary and review, some embodiments provide a negative electrode active material that exhibits improved expansion characteristics and excellent cycle-life characteristics. Another embodiment may provide a rechargeable lithium battery including the negative electrode active material.
[0144] Example embodiments have been disclosed herein, and although specific terms are employed, they are used and interpreted only in a general and descriptive sense and not for purposes of limitation. In some cases, as will be apparent to one of ordinary skill in the art upon filing this application, unless otherwise specifically noted, features, characteristics, and / or elements described in conjunction with a specific embodiment may be used alone or in combination with features, characteristics, and / or elements described in conjunction with other embodiments. Therefore, it will be understood by those skilled in the art that various changes in form and detail may be made without departing from the spirit and scope of the invention as set forth in the appended claims.
Claims
1. A negative electrode active material, comprising: a silicon nanoparticle comprising an amorphous carbon coating on a surface of the silicon nanoparticle; as well as hole, in: The negative electrode active material has a sphericity of 0.9 to 1.0 represented by Equation 1, The pores include mesopores, and a ratio of the volume of the mesopores of the negative electrode active material relative to the total pore volume is 30% or more and less than 70%, and [Equation 1] Sphericity S = 4π × A / B 2 In Equation 1, A is the area of the negative electrode active material, and B is the perimeter of the shape of the negative electrode active material.
2. The negative electrode active material according to claim 1, wherein The mesopores have a size of 2 nm to 50 nm.
3. The negative electrode active material according to claim 1, wherein The ratio of the mesopore volume of the negative electrode active material to the total pore volume is 30% to 68%.
4. The negative electrode active material according to claim 1, wherein: The negative electrode active material has a span defined by Equation 2 of 1.1 to 1.6, and [Equation 2] Span = (D90-D10) / D50 In Equation 2, D10 refers to the diameter of the negative electrode active material particles whose cumulative volume is 10% by volume in the particle size distribution, D50 refers to the diameter of the negative electrode active material particles whose cumulative volume is 50% by volume in the particle size distribution, and D90 refers to the diameter of the negative electrode active material particles whose cumulative volume is 90% by volume in the particle size distribution.
5. The negative electrode active material according to claim 4, wherein The span of the negative electrode active material is 1.1 to 1.
55.
6. The negative electrode active material according to claim 4, wherein The span of the negative electrode active material is 1.1 to 1.
5.
7. The negative electrode active material according to claim 1, wherein The sphericity of the negative electrode active material is 0.92 to 0.
98.
8. The negative electrode active material according to claim 1, wherein The sphericity of the negative electrode active material is 0.92 to 0.
95.
9. The negative electrode active material according to claim 1, wherein The negative electrode active material also includes a polymer layer on the amorphous carbon coating layer.
10. The negative electrode active material according to claim 9, wherein The polymer layer includes polyvinyl alcohol and polyacrylic acid.
11. The negative electrode active material according to claim 9, wherein The polymer layer includes a copolymer of polyvinyl alcohol and polyacrylic acid.
12. The negative electrode active material according to claim 11, wherein The copolymer includes a cross-linked copolymer of the polyvinyl alcohol and the polyacrylic acid.
13. The negative electrode active material according to claim 1, wherein The negative electrode active material has 0.5 m 2 / g to 2m 2 / g specific surface area.
14. The negative electrode active material according to claim 1, wherein The negative electrode active material has 0.8m 2 / g to 2m 2 / g specific surface area.
15. The negative electrode active material according to claim 1, wherein The negative electrode active material has 0.8m 2 / g to 1.5m 2 / g specific surface area.
16. The negative electrode active material according to claim 1, wherein The total pore volume of the negative electrode active material is 0.001 cm 3 / g to 0.05cm 3 / g.
17. The negative electrode active material according to claim 1, wherein The silicon nanoparticles have a particle size of 1 nm to 1000 nm.
18. The negative electrode active material according to claim 1, wherein The amorphous carbon coating has a thickness of 1 nm to 2 μm.
19. A rechargeable lithium battery, comprising: A negative electrode comprising a negative electrode active material according to any one of claims 1 to 18; Positive electrode; as well as Electrolytes.
20. The rechargeable lithium battery according to claim 19, wherein: The negative electrode includes the negative electrode active material as a first negative electrode active material, and further includes crystalline carbon as a second negative electrode active material.